2020
DOI: 10.1182/blood-2020-142750
|View full text |Cite
|
Sign up to set email alerts
|

FT576: Multi-Specific Off-the-Shelf CAR-NK Cell Therapy Engineered for Enhanced Persistence, Avoidance of Self-Fratricide and Optimized Mab Combination Therapy to Prevent Antigenic Escape and Elicit a Deep and Durable Response in Multiple Myeloma

Abstract: Multiple redundancy within the spectrum of an immune response is required to prevent antigen escape or adaptation of the targeted population to host defenses. As adoptive cell therapies continue to evolve, multi-modal engineering of effector cells offers the prospect of tackling increasingly complex disease settings such as multiple myeloma (MM), where targeting of a single tumor associated antigen is frequently confounded by antigen shedding and escape variation resulting in the inability to develop a curativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…FT596 and FT576, cell products for B-cell malignancies and MM, respectively, are investigational and off-the-shelf CAR-NK cell products derived from a human clonal master iPSC line engineered with anti-tumor abilities. These functional cell products can be manufactured on a large scale to support multi-dose therapeutic strategies and on-demand dose availability (60)(61)(62).…”
Section: Nk Cellsmentioning
confidence: 99%
“…FT596 and FT576, cell products for B-cell malignancies and MM, respectively, are investigational and off-the-shelf CAR-NK cell products derived from a human clonal master iPSC line engineered with anti-tumor abilities. These functional cell products can be manufactured on a large scale to support multi-dose therapeutic strategies and on-demand dose availability (60)(61)(62).…”
Section: Nk Cellsmentioning
confidence: 99%
“…The preliminary data indicated that up to six doses of FT516 cells were safe and tolerable. Genetically modified iPSC (CD38 knockout, overexpressing IL15RF, hnCD16, BCAM-CAR) derived NK cell therapy (FT576) targeting relapsed/refractory MM in vitro and in xenograft mouse models has shown efficacy alongside good synergy with monoclonal antibodies daratumumab/elotuzumab/anti-CD19 [113]. The clinical trials using iPSC-based CAR-NK targeting hematological malignancies are listed in Table 3.…”
Section: Identification Of Therapeutic Targets Using Ipscs-clinical and Translational Implicationsmentioning
confidence: 99%
“…Other current investigational therapies include oncolytic targeted vaccines [101][102][103][104], enhancements to existing T cell-directed therapies [105], and other types of adoptive cell therapy aside from CAR-T cells [106,107]. Trials studying chemotherapy agents such as bendamustine and arsenic have decreased in recent years in favor of targeted therapeutics [108,109], although there are ongoing efforts to examine the efficacy of these agents in specialized populations [110][111][112].…”
Section: Other Investigational Therapiesmentioning
confidence: 99%